The impact of intercellular communication for the generation of complex multicellular prevascularized tissue equivalents. Issue 3 (13th December 2019) - Heller, Martin; Bauer, Heide‐Katharina; Schwab, Roxana; Blatt, Sebastian; Peters, Katharina; Nezi‐Cahn, Sandra; Unger, Ronald E.; Hasenburg, Annette; Brenner, Walburgis
Abstract: In reconstructive surgery the use of prevascularized soft tissue equivalents is a promising approach for wound coverage of defects after tumor resection or trauma. However, in previous studies to generate soft tissue equivalents on collagen membranes, microcapillaries were restricted to superficial areas. In this study, to understand which factors were involved in the formation of these microcapillaries, the levels of the angiogenic factors vascular endothelial growth factor (VEGF), Interleukin‐8 (IL‐8), and basic fibroblast growth factor (bFGF) in the supernatants of the tissue equivalents were examined at various time points and conditions. Additionally, the influence of these factors on viability, proliferation, migration, and tube formation in monocultures compared to cocultures of fibroblast and endothelial cells was examined. The results showed that VEGF production was decreased in cocultures compared to fibroblast monocultures and the lowest VEGF levels were observed in endothelial cell monocultures. Additionally, the highest levels of IL‐8 were observed in cocultures compared to monocultures. Similar results were observed for bFGF with lowest levels seen within the first 24 hr and highest levels in cocultures. VEGF and IL‐8 were shown to promote endothelial cell viability, proliferation and migration and angiogenic parameters such as tube density, total tube length, and number of tube branches. Addition of VEGF and IL‐8 to cocultures resulted in accelerated and denser formation of capillary‐like structures. The results indicate that VEGF, IL‐8, and bFGF strongly influence cellular behavior of endothelial cells and this information should be useful in promoting the formation of microcapillary‐like structures in complex tissue equivalents.